Multi criterion Analysis for Ground water Potential Zones along River Gostani and surroundings of Visakhapatnam, Andhra Pradesh, India. - M.Ganesh, K; Jai Sankar, G; Jagannadha Rao, M; C.S.V. Prasad, A (International Journal of Engineering and Technology, 2018)
The present study is to make an analysis of the groundwater potential zones along Gostani river and the nearby areas.Â The data is collected from the field concern department and through internet to make a study.Â For the study seven parameters have been taken into consideration like geology, geomorphology, drainage, slope, soil, land use / land cover and lineaments.Â Â Thematic maps prepared and reclassified under Geographical Information System (G.I.S) environment.Â Weightage for each theme and its classes have been allocated by making use of weighted overlay analysis and then Analytical Hierarchical Process in Arc G.I.S. so as to find out the result.Â Â